2021
DOI: 10.1186/s12957-021-02165-x
|View full text |Cite
|
Sign up to set email alerts
|

Four cases of completion lobectomy for locally relapsed lung cancer after segmentectomy

Abstract: Background Although completion lobectomy is the treatment of choice for local recurrence of non-small cell lung cancer after segmentectomy, few cases have been reported. We report four patients who underwent completion lobectomies for staple line recurrence after segmentectomy for stage I non-small cell lung cancer. Case presentation Three women aged 65, 82, and 81 years underwent completion lower lobectomy after superior segmentectomy of the same … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 8 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…Only a handful of studies have reported the surgical outcomes of CL after segmentectomy. 5 , 6 , 7 , 8 , 9 , 10 Completion lobectomy after segmentectomy has been associated with rare adverse circumstances, including complications or local recurrences in the remaining lobe, as well as unexpected nodal involvement, which was first proposed by Omasa et al 5 In the current study, we used a similar classification for the included 41 patients. A greater percentage of complications (64%) occurred in the short interval‐to‐CL group, while a higher rate of local recurrence (93%) occurred in the long interval‐to‐CL group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a handful of studies have reported the surgical outcomes of CL after segmentectomy. 5 , 6 , 7 , 8 , 9 , 10 Completion lobectomy after segmentectomy has been associated with rare adverse circumstances, including complications or local recurrences in the remaining lobe, as well as unexpected nodal involvement, which was first proposed by Omasa et al 5 In the current study, we used a similar classification for the included 41 patients. A greater percentage of complications (64%) occurred in the short interval‐to‐CL group, while a higher rate of local recurrence (93%) occurred in the long interval‐to‐CL group.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies have reported, completion upper lobectomy is technically tougher than completion lower lobectomy because of anatomical features, presence of adhesions around the main PA at the hilum, and effect of previous superior mediastinal nodal dissection. 7 In terms of technical issues, some authors have addressed the use of simultaneous division of the PA and lung parenchyma with a stapler to manage tight adhesions. 8 , 9 Simultaneous stapling of the bronchus and PA is generally not preferred because of the risk of staple line bursts, bronchopleural fistula, and massive bleeding; however, no adverse events resulting from simultaneous stapling have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, performing CL after sublobar resection in the same lobe or hemithorax may be complicated by severe adhesions around the hilar structures, especially the pulmonary artery [ 12 , 13 ]. Only a few studies, which included a low number of patients, have reported the outcomes of CL after locoregional recurrence [ 9 , 12 - 15 ]. Therefore, the purpose of this study was to determine the surgical and oncologic outcomes of CL in patients with locoregionally recurrent stage I NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…One of the factors related to locoregional recurrence after segmentectomy was reported to be inadequate surgical margins. 10 It is considered that segmentectomy for inner-located lung cancer may result in shorter surgical margins due to the closer distance to adjacent segments or hilar area compared with outer-located cancer; therefore, the oncological validity of segmentectomy for inner-located NSCLC should be evaluated carefully.…”
mentioning
confidence: 99%